Aba Ginoong Maria [videorecording] the great virgins of Luzon - Medina, Susan Calo; Quintos, Floy (Travel time, 1996)
A documentary on the great Virgins of Luzon. It presents the Blessed Virgin Mary's historical significance, her role and importance of Filipino culture. It features the virgins of La Naval, De Guia, Dela Paz de Buenviaje and Penafrancia.